MacBride on truth in truthmaking. (8th December 2015) - Simpson, Matthew
Abstract: Fraser MacBride has argued that deflationism about truth makes the truthmaker principle, that every truth has a truthmaker, implausible. This is because on a deflationary view, the truthmaker principle is a mere abbreviation of a conjunction of claims which have no independent motivation. In this article, I argue that this claim is false: deflationism does not entail that the truthmaker principle is a mere abbreviation of such a conjunction, because the claims MacBride focuses on are in fact irrelevant to the motivations for truthmaker theory. Moreover, deflationists can consistently articulate and accept such motivations. Deflationism has no bearing on the plausibility of the truthmaker principle.